2006
DOI: 10.2214/ajr.04.1715
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Carpal Tunnel Syndrome: Accuracy of Gray-Scale and Color Doppler Sonography

Abstract: Color Doppler sonography is more accurate than gray-scale sonography for characterizing median nerve involvement in patients with suspected carpal tunnel syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
162
4
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(181 citation statements)
references
References 38 publications
6
162
4
8
Order By: Relevance
“…We monitored adverse events related to electroacupuncture and splinting using a previously published approach. 40 Details of outcomes and measurement methods for adverse events can be found in Appendix 1.…”
Section: Discussionmentioning
confidence: 99%
“…We monitored adverse events related to electroacupuncture and splinting using a previously published approach. 40 Details of outcomes and measurement methods for adverse events can be found in Appendix 1.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 When the pressure on a peripheral nerve is experimentally increased, a reduction of intraneural microcirculation occurs with subsequent breakdown of the blood nerve barrier and the formation of intraneural and extraneural edema. 4 In CTS, swelling of the median nerve has been identified intra-operatively, 5,6 with ultrasound imaging 7 and with conventional magnetic resonance imaging (MRI). 8,9 If present for prolonged periods, intraneural edema may lead to potentially irreversible fibrotic changes.…”
mentioning
confidence: 99%
“…Intraneural vascularity has been proposed as an additional parameter in the diagnosis of CTS, sometimes being the only detectable finding [34,35]. Recent studies have shown that endoneural hypervascularity is correlating with the severity of the median nerve lesions evaluated through electrophysiologic studies [36,37].…”
Section: Discussionmentioning
confidence: 99%